Pemanfaatan Waktu Luang dengan Edukasi tentang Pencegahan Penyakit Malaria di Dusun Sukadana Kabupaten Lombok Barat - Komala Dini (Nuras : Jurnal Pengabdian Kepada Masyarakat, 2025)
Malaria is still a significant public health problem in several regions in Indonesia, including Sukadana Hamlet, Lelede Village, Kediri District, West Lombok Regency. Lack of public knowledge about the causes, transmission, and prevention of malaria is the main factor in the high number of cases of this disease. This community service activity aims to utilize people's free time productively through education about malaria prevention. The methods used in this activity include interactive counseling, discussions, and showing educational videos. This activity targets various age groups, from teenagers to the elderly, with the hope of creating collective awareness in preventing the spread of malaria. The results of the activity showed an increase in public understanding of the importance of maintaining environmental cleanliness, using mosquito nets when sleeping, and recognizing early symptoms of malaria. This education is expected to be the first step in reducing the incidence of malaria in Sukadana Hamlet in a sustainable manner.